Penggunaan Power Point Game pada Materi Persegi Panjang Kelas VII SMP Muhammadiyah Pagaralam - Okta Wirajaya; Widiawati Widiawati; Chika Rahayu (Institut Agama Islam Negeri Curup, 2019)
The purpose of this study was to find out the learning outcomes of students after the use of Power Point Game on the study of Rectangles in class VII of Pagaralam Muhammadiyah Middle School. The design used in this study is a one shoot case study which is an experiment that is implemented without using a companion group. This study was only conducted in class VII 4, which amounted to 31 people. Based on the data analysis, the results of the post test were obtained with a class average value of 82.8. Thus it can be concluded that the use of Power Point learning media games on rectangular material can improve the learning outcomes of Grade VII students at Muhammadiyah Middle School Pagaralam.